2022
DOI: 10.1007/s40097-022-00501-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-bright green carbon dots with excitation-independent fluorescence for bioimaging

Abstract: Current and future diagnostics urgently need imaging agents that are non-toxic and superior to clinically used small molecule dyes. Herein, we have developed luminescent green light-emitting carbon dots (GCDs) via a single-step hydrothermal reaction using a low-cost chemical precursor, p-toluenesulfonic acid. The GCDs exhibit excitation-independent fluorescence (FL) emission with the photoluminescence quantum yield of 70% and no FL quenching up to 1.25 mg/mL. The GCDs exhibit negligible cytotoxicity up to 250 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…These data demonstrated that GB-CDs have long shelf-life stability and great preparation reproducibility, great merits for commercial use. Similarly, green light-emitting CDs prepared by hydrothermal treatment of p -toluenesulfonic acid and ethylenediamine showed a good stability with a charge of −18 mV …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data demonstrated that GB-CDs have long shelf-life stability and great preparation reproducibility, great merits for commercial use. Similarly, green light-emitting CDs prepared by hydrothermal treatment of p -toluenesulfonic acid and ethylenediamine showed a good stability with a charge of −18 mV …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, green light-emitting CDs prepared by hydrothermal treatment of p-toluenesulfonic acid and ethylenediamine showed a good stability with a charge of −18 mV. 62 2.6. Fe 3+ Detection in Mitochondria Using GB-CDs.…”
Section: Gb-cds Canmentioning
confidence: 96%
“…Therefore, the solution concentration has a great influence on the QY of red light emission. 51 Considering the featured GQDs with long-wavelength emission and high QY, the as-prepared GQDs have been proposed to serve as an intracellular imaging probe. Hence, the properties of aqueous the GQD solutions have been studied.…”
Section: Resultsmentioning
confidence: 99%
“…29 However, these bioconjugates can only be activated by 470 nm light irradiation, thus limiting deep tissue penetration. Carbon nanodots (Cdots) have attracted major interest as fluorescent sub 10 nm carbon nanomaterials for biomedical applications due to their ease of synthesis, 30,31 facile surface functionalization, 32 biocompatibility, 33 chemical stability and photostability, 34 photoluminescence (PL), 35 and efficient twophoton absorption even at low irradiation power. 36,37 Several of their photophysical and biological properties are comparatively better than those of easily photobleachable fluorescent organic dyes and conventional toxic semiconductor nanomaterials such as heavy-metal-containing quantum dots.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanodots (Cdots) have attracted major interest as fluorescent sub 10 nm carbon nanomaterials for biomedical applications due to their ease of synthesis, , facile surface functionalization, biocompatibility, chemical stability and photostability, photoluminescence (PL), and efficient two-photon absorption even at low irradiation power. , Several of their photophysical and biological properties are comparatively better than those of easily photobleachable fluorescent organic dyes and conventional toxic semiconductor nanomaterials such as heavy-metal-containing quantum dots . Recently, conjugates composed of carbon nanodots and a PS have been reported for NIR two-photon activated PDT, including (a) carbon quantum dot–protoporphyrin IX sensitizers that were activated at 800 nm irradiation (80 mW femtosecond (fs) laser power) by a two-photon excitation process, (b) carbon nanodot–5,10,15,20-tetrakis­(1-methyl-4-pyridinio)­porphyrin tetra­( p -toluenesulfonate) conjugates that were excited with fs lasers (160 mW/cm 2 ) at 700 nm, (c) a noncovalent nanocomposite from single-walled carbon nanotubes and Ru­(II) complexes for efficient dual phototherapy employing an 808 nm diode laser (0.25 W/cm 2 ), and (d) a nanohybrid composed of carbon nanodots and a Ru­(II) complex for lysosome-targeted PDT using an 810 nm laser (100 mW, 100 fs) .…”
Section: Introductionmentioning
confidence: 99%